Meteorological regime controls on PM2.5 and O3 variability in the Sichuan Basin: insights from a hybrid causal-machine learning analysis - Yuyi Du; Xin Qi; Miao Feng; Hanxiong Che; Fumo Yang; Xin Long; Dasheng Huang; Shumin Zhang; Chao Peng; Yang Chen (Atmospheric Environment, 2026)

Intraseasonal variability and eddy-induced structural modulation of the North Pacific intermediate water revealed by multi-mooring observations - Qiang Ren; Yansong Liu; Yansheng Zhang; Shumin Tu; Wei Huang; Feng Nan; Ran Wang; Xinyuan Diao; Jianfeng Wang; Xinchuang Liu; Zifei Chen; Fei Yu (Ocean Science, 2026)
The North Pacific Intermediate Water (NPIW) plays an important role in regulating thermohaline structure and biogeochemical distributions in the North Pacific. However, limited continuous observations have hindered our understanding of its short-term variability and structural response to mesoscale processes. Based on 1 year mooring observations from three sites (M1–M3) in the western North Pacific, this study investigates the intraseasonal structural variability of the NPIW and its modulation by mesoscale eddies. The NPIW thickness exhibits pronounced intraseasonal variability, with a dominant period of approximately 60–80 d that is coherent among the three mooring sites. Unlike previous studies that mainly focused on temperature and salinity anomalies, this study introduces NPIW thickness as a structural diagnostic parameter to characterize the vertical compression and expansion of the intermediate layer associated with mesoscale variability. The results reveal a clear inverse relationship between NPIW thickness and salinity, indicating that anticyclonic conditions are generally associated with thinner and more saline intermediate layers, whereas cyclonic conditions correspond to thicker and relatively fresher layers. Spatial composite analyses further show that thickness and salinity responses exhibit clear regional differences, with stronger variability near the western boundary, likely related to complex water-mass redistribution and possible mixing processes. These findings provide quantitative observational evidence for intraseasonal variability in NPIW thickness and highlight its usefulness as a diagnostic indicator for mesoscale–intermediate water interactions in the North Pacific.

Decadal evolution and dynamics of the Longxigou landslide’s composite deforming surface revealed by space-air-ground investigation strategy - Shumin Feng; Keren Dai; Zhiyu Li; Peng Zeng; Weiwei Tian; Xiquan Wang; Yanfei Kang; Hong Xu; Lichuan Chen (Landslides, 2026)

β-Sitosterol: a Common Compound in Hundreds of Traditional Chinese Medicine Treatments for Infertility and its Effects on Human Ovarian Granulosa Cells - Yu Sun; Gengchen Feng; Ziyi Yang; Yimeng Li; Shumin Li; Shigang Zhao (Phenomics, 2026)

NiV-OH/CoNi-MOF heterostructures enabling intercalation–phase transition synergy for high-energy asymmetric supercapacitors - Yina Xiang; Shumin Qin; Shuang Luo; Hui Zhou; Guochuang Tian; Feng Zhan; Jien Li (Chemical Engineering Journal, 2026)

Multi-pathway vegetation restoration drives differential carbon sequestration regulated by hydrogeological conditions in Lijiang River Basin - Shumin Feng; Xiuqin Wu; Jianhua Cao; Hui Yang; Fen Huang; Liankai Zhang; Jinxing Zhou (CATENA, 2026)

Effects of photochemical and aqueous-phase oxidation on secondary formation during the 31st FISU Summer World University Games, 2023 - Xiaoling Zeng; Zhier Bao; Jiawei Zhou; Guangming Shi; Li Zhou; Shumin Zhang; Xin Qi; Keding Lu; Chongzhi Zhai; Zhenliang Li; Xin Li; Chao Peng; et al. (Journal of Environmental Sciences, 2026)

Lithological predominance in landslide distribution in western Sichuan (China), revealed by multi-sensor remote sensing analysis - Xianlin Shi; Tao Yin; Keren Dai; Wei Sun; Mahdi Motagh; Chen Liu; Shumin Feng; Qiang Xu (Advances in Space Research, 2026)

Macrophage cytoskeletal and immune responses to photoaged and gastrointestinal-transformed polylactic acid micro/nanoplastics with protein corona - Xuri Wu; Feng Tan; Han Zhang; Liping Huang; Yan Wang; Xin He; Rui Cai; Shumin Li (Journal of Hazardous Materials, 2025)

Carbon sequestration in soil affected by mineral-doped biochar: Roles of soil aggregate and microbial community - Rongchuan Ye; Yan Ma; Zixuan Wang; Ting Yang; Yanbin Du; Shumin Wu; Yanfang Feng; Lisha Wang; Wenjing Song (Journal of Cleaner Production, 2025)

Improving the gel properties of Nemipterus virgatus myosin gel using soy protein isolate-stabilized Pickering emulsion - Shouyu Feng; Cikun Liu; Yanwei Liu; Shumin Yi; Jianrong Li; Bin Zhang; Xuepeng Li (Food Chemistry, 2025)

Ultra-fast preparing carbon nanotube-supported Ni-Fe bimetallic compounds as robust electrocatalysts for oxygen evolution reaction - Taotao Gao; Qi An; Shumin Yu; Xiangrui Feng; Bing Li; Yanyan Huang; Hai Lan; Dan Xiao (Fuel, 2025)

Correlation between pollen morphology, karyotype, floral pigments, and scent components and morphological classification of 15 species and hybrids of Syringa L - Feng Qian; Xiaoou Zhai; Ziyin Cheng; Zhenyu Yu; Guoqiang Chen; Yan Gao; Liwei Sun; Li Fang; Shumin Yang; Shaoqi Xu; Huimin Liu (The Science of Nature, 2025)

Factors influencing the dissolution rate of radon gas in water - Xiongjie Zhang; Li Feng; Ye Zhang; Yangyang Feng; Bao Wang; Haixian Zhou; Shumin Zhou (Journal of Environmental Radioactivity, 2024)

GWSM4C: A global wave surrogate model for climate simulation based on a convolutional architecture - Quan Jin; Xingjie Jiang; Feng Hua; Yongzeng Yang; Shumin Jiang; Chen Yu; Zhenya Song (Ocean Engineering, 2024)

Arsenic sulfide enhances radiosensitivity in rhabdomyosarcoma via activating NFATc3-RAG1 mediated DNA double strand break (DSB) - Yu Cai; Chuanying Zhu; Shumin Lu; Ting Kang; Shuxian Chen; Zhuowei Feng; Siyu Chen (Chemico-Biological Interactions, 2024)

Development and characterization of Artemisia argyi essential oil-loaded nanoemulsion for sustainable weed control: Enhanced stability, amplified activity, protected non-target - Hong Chen; Jinxin Li; Xinglei Chen; Likun Mei; Shumin Feng; Pengfei Duan; Huixia Cai; Kaili Qu; Jingyi Zhang; Yuhuan Miao; Dahui Liu (Journal of Cleaner Production, 2024)

Unlocking the potential of biochar: an iron-phosphorus-based composite modified adsorbent for adsorption of Pb(II) and Cd(II) in aqueous environments and response surface optimization of adsorption conditions - Xu Li; Yuan Chi; Feng Ma; Xiaoxin Wang; Rui Du; Zhipeng Wang; Xiaoyan Dang; Chaoyue Zhao; Yanping Zhang; Shumin He; Youzhao Wang; Tong Zhu (Environmental Science and Pollution Research, 2024)

OcBSA: An NGS-based bulk segregant analysis tool for outcross populations - Lingkui Zhang; Yanfeng Duan; Zewei Zhang; Lei Zhang; Shumin Chen; Chengcheng Cai; Shaoguang Duan; Kang Zhang; Guangcun Li; Feng Cheng (Molecular Plant, 2024)

Using machine learning to trace the pollution sources of disinfection by-products precursors compared to receptor models - Yuan Xiao; Shunjun Ma; Shumin Yang; Huan He; Xin He; Cheng Li; Yuheng Feng; Bin Xu; Yulin Tang (Science of The Total Environment, 2024)

Stimuli-activatable PROTACs for precise protein degradation and cancer therapy - Jing Gao; Lei Yang; Shumin Lei; Feng Zhou; Huijun Nie; Bo Peng; Tianfeng Xu; Xiaohua Chen; Xiaobao Yang; Chunquan Sheng; Yu Rao; Kanyi Pu; et al. (Science Bulletin, 2023)

Suggestion on further strengthening ultra-low emission standards for PM emission from coal-fired power plants in China - Jianguo Deng; Shumin Wang; Jiawei Zhang; Yi Zhang; Jingkun Jiang; Yongzheng Gu; Tao Han; Lei Feng; Jian Gao; Lei Duan (Journal of Environmental Sciences, 2023)

Epigenetic Regulation of Spermatogonial Stem Cell Homeostasis: From DNA Methylation to Histone Modification - Shumin Zhou; Shenglei Feng; Weibing Qin; Xiaoli Wang; Yunge Tang; Shuiqiao Yuan (Stem Cell Reviews and Reports, 2021)

Anxiolytic Effect of Increased NREM Sleep after Acute Social Defeat Stress in Mice - Xiang Feng; Hui-Ying Zhao; Yu-Jin Shao; Hui-Fang Lou; Li-Ya Zhu; Shumin Duan; Yan-Qin Yu (Neuroscience Bulletin, 2020)
Social defeat stress (SDS) plays a major role in the pathogenesis of psychiatric disorders like anxiety and depression. Sleep is generally considered to involve recovery of the brain from prior experience during wakefulness and is altered after acute SDS. However, the effect of acute SDS on sleep/wake behavior in mice varies between studies. In addition, whether sleep changes in response to stress contribute to anxiety is not well established. Here, we first investigated the effects of acute SDS on sleep/wake states in the active period in mice. Our results showed that total sleep time (time in rapid eye-movement [REM] and non-REM [NREM] sleep) increased in the active period after acute SDS. NREM sleep increased mainly during the first 3 h after SDS, while REM sleep increased at a later time. Then, we demonstrated that the increased NREM sleep had an anxiolytic benefit in acute SDS. Mice deprived of sleep for 1 h or 3 h after acute SDS remained in a highly anxious state, while in mice with ad libitum sleep the anxiety rapidly faded away. Altogether, our findings suggest an anxiolytic effect of NREM sleep, and indicate a potential therapeutic strategy for anxiety.

Insecticide resistance status and detoxification enzymes of wheat aphids Sitobion avenae and Rhopalosiphum padi - Liuping Zhang; Hong Lu; Kun Guo; Shumin Yao; Feng Cui (Science China Life Sciences, 2017)

Simulation of the spatial stresses due to territorial land development on Yellow River Delta Nature Reserve using a GIS-based assessment model - Baolei Zhang; Qiaoyun Zhang; Qingyu Feng; Bohao Cui; Shumin Zhang (Environmental Monitoring and Assessment, 2017)

Assessment on characteristics of LUCC process based on complex network in Modern Yellow River Delta, Shandong Province of China - Baolei Zhang; Le Yin; Shumin Zhang; Chaoyang Feng (Earth Science Informatics, 2016)